TINGKAT KETERAMPILAN PASSING BAWAH PADA PERMAINAN BOLA VOLI - Dea Chisva Islami (STKIP Muhammadiyah Kuningan, 2021)
In the study, applying the volleyball bottom passing exercise. With practice being bounced off the wall and thrown by a friend in pairs. This study uses the research method of women's volleyball experiment at SMPN 1 Cilebak, totaling 20 people. The results of this research and development are data on the pretest posttest scores using the SPSS 22.0 for Windows program with a significant level of 0.05. The results of this study indicate that the increase in passing over volleyball is 18.90%. From the results of the research that has been done, it can be concluded that with the practice of passing down volleyball, it can be developed and applied in the training process. Based on these results, it can be used as a volleyball passing practice and at the same time an output product of a volleyball bottom passing exercise model.